Canary Production - Fatma Yenilmez (Turkish Journal of Agriculture: Food Science and Technology)
Canary (Serinus canarius) is one of the most beautiful cage birds. They are small and delicate songbird species. Their origin is the Canary Islands in the Atlantic Ocean. They were first brought to Europe by the Spanish sailors in 1478. Than Britain, Germany, France, Netherlands and Italy were started professional canary breeding. The wild ones live in flocks, mostly on the edge of wooded lakes and creeks. While the color of canaries grown in cages is completely yellow, the wild ones are gray-green. Sound in the wild canary is stronger and more impressive. There are 3 types of canaries commonly produced. These are “Song canaries”, “Color canaries” and “Form canaries”. Nowadays they are often produced for their beautiful color and sound. This article gives brief information about canaries and to provide resources to enthusiasts who want to do produce has been prepared.